Aims and problems of diversification - Christian Wilhelms (Intereconomics, 1972)
Notwithstanding the Importance attributed to international commodity agreements, the long-term solution to the developing nations' economic problems must be sought in diversification. On this subject the HWWA-Institut für Wirtschaftsforschung-Hamburg (The Hamburg Institute for International Economics) prepared a study for the Federal Ministry for Economics and Finance. The following article summarises the main results.
Keywords: 330; Development Spectrum